Gastric carcinoma's primary presentation as multiple cutaneous nodules throughout the body. (2022) - Bajoghli, Amir A; Piselli, Alexandra; Kemprecos, Helen; Khosravi, Hamed; Cardis, Michael A.; Noel, Marcus S.
Abstract: Cutaneous metastasis resulting from internal primary tumors remains a rare phenomenon. The prompt recognition of these metastases is important, as they are an indicator of advanced disease and poor prognosis. We report the case of a 44-year-old Caucasian man presenting with a four-month history of multiple cutaneous nodules on the face, trunk, and upper extremities. Results from skin biopsy revealed strands and cords of atypical cells concerning for poorly differentiated metastatic carcinoma. An esophagogastroduodenoscopy was performed and a poorly differentiated signet-ring type invasive adenocarcinoma at the lesser curvature of the stomach was found. As the cancer had already metastasized to the skin and bones, the patient was started on chemotherapy with an oxaliplatin-based regimen and denosumab for the bone metastases, with resultant objective response and diagnostic control for greater than one year to the present date.